Efektivitas Program Kartu Indonesia Pintar (KIP-K) di Universitas Negeri Gorontalo - Zelin A. Usman; Arifin Tahir; Sri Yulianty Mozin (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
This study is motivated by the importance of the effectiveness of the Indonesia Smart Card for Higher Education Program (KIP-K) in expanding access to higher education for students from low-income families at Universitas Negeri Gorontalo. This study aims to analyze the effectiveness of the implementation of the KIP-K Program based on the aspects of goal attainment, integration, and adaptation. The research employed a descriptive qualitative approach, with data collected through interviews, observation, and documentation. The data were analyzed through the stages of data reduction, data display, and conclusion drawing and verification. In terms of goal attainment, the program helps students continue their education, although several challenges remain, including limited quotas, inaccurate targeting, and suboptimal on-time graduation. In terms of integration, coordination among program administrators, faculties, departments, students, and banking partners has functioned quite well, although academic services for recipients have not been entirely equal. In terms of adaptation, the program has shown the ability to adjust to policy changes and students’ needs through periodic evaluation and adjustments to the disbursement mechanism. The implication is that stronger targeting accuracy, academic assistance, service quality, and evaluation systems are needed to ensure more optimal and sustainable program implementation.